Investigation into creep‐to‐rupture of SIMP steel in stagnant LBE at 300–450°C. Issue 5 (13th January 2022) - Liao, Qing; Li, Bingsheng; Ge, Fangfang; Wang, Renda; Zhang, Hongpeng; Krsjak, Vladimir; Sheng, Yanbin
Abstract: Ferritic/martensitic steel was chosen as a primary candidate structural material for China Initiative Accelerator Driven System (CiADS) which started in 2015. A new kind of tempered martensitic steel, Steel of Institute of Modern Physics (SIMP), was designed to meet the requirements of the special operating environment. Structural materials suffer from liquid Pb‐Bi corrosion and liquid metal wetting at 450°C. Liquid metal wetting can seriously affect the mechanical properties of structural materials due to the decrease in surface energy and transition from martensitic laths to ferritic grains. Creep‐to‐rupture of SIMP steel was explored in stagnant liquid Pb‐Bi eutectic at 450°C. The possible reasons for creep‐to‐rupture are discussed. The results of the present study provide a new insight into challenges related to the application of SIMP steel in CiADS. Abstract : Creep‐to‐rupture of a new kind of tempered martensitic steel (SIMP) was explored in stagnant liquid Pb‐Bi eutectic at 450°C. The possible reasons for creep‐to‐rupture are discussed. The results of the present study provide new insight into challenges related to would be valuable for the application of SIMP steel in the China Initiative Accelerator Driven System.